2021
DOI: 10.33448/rsd-v10i5.14936
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico dos doadores de sangue infectados pelo vírus HIV, no Estado do Piauí, Brasil

Abstract: A doação sanguínea representa uma importante ação de saúde pública em todo o país, embora apresente altos índices de transmissibilidade e infecção pelo vírus da imunodeficiência humana (HIV). Nessa perspectiva, o presente estudo tem como objetivo avaliar o perfil epidemiológico e a prevalência de HIV nos indivíduos que fizeram doação de sangue no Centro de Hematologia e Hemoterapia do Piauí (HEMOPI), no período de 2008 a 2013. O estudo possui caráter retrospectivo, descritivo, de base documental e quantitativo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This is related to the greater efficiency of transmission from men to women and the greater number of sexual exposures throughout life (Glória et al, 2015;Silva et al, 2018). The predominance of single (including divorced and widowed) individuals recorded in the present study may be related to a greater risk of sexual transmission associated with multiple partners and unprotected sex Silva & Silva, 2015;Proietti et al, 2005). Donors with high school completed were more frequent for HTLV seropositivity, which may be a reflection of the reduced access to information on basic health, in general, and on the prevention of sexually transmitted infections, in particular (Glória et al, 2015;Dourado et al, 2003).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This is related to the greater efficiency of transmission from men to women and the greater number of sexual exposures throughout life (Glória et al, 2015;Silva et al, 2018). The predominance of single (including divorced and widowed) individuals recorded in the present study may be related to a greater risk of sexual transmission associated with multiple partners and unprotected sex Silva & Silva, 2015;Proietti et al, 2005). Donors with high school completed were more frequent for HTLV seropositivity, which may be a reflection of the reduced access to information on basic health, in general, and on the prevention of sexually transmitted infections, in particular (Glória et al, 2015;Dourado et al, 2003).…”
Section: Discussionmentioning
confidence: 51%
“…No systematic epidemiological studies of the prevalence of HTLV are available for the general population of Brazil, although studies of blood donors do provide some insights into infection rates. The seroprevalence of this virus in blood donors varies considerably among Brazilian states (Figure 2), with the highest prevalence typically occurring in the North (Acre, Amazonas, Amapá, Pará, Rondônia, Roraima, and Tocantins states) and Northeast (Alagoas, Bahia, Ceará, Maranhão, Paraíba, Pernambuco, Piauí, Rio Grande do Norte, and Sergipe) (Semeão et al, 2015;Catalan-Soares et al, 2005;Morais et al, 2017;Galvão-Castro et al, 1997;Ribeiro-Lima et al, 1999;Maneschy et al, 2021;Silva & Silva, 2015;Ribeiro et al, 2018), while the lowest rates are found in the South (Paraná, Rio Grande do Sul, and Santa Catarina) and Southeast (Espírito Santo, Minas Gerais, Rio de Janeiro, and São Paulo) regions (Semeão et al, 2015;Pereira & Bonafé, 2015;Catalan-Soares et al, 2005;Galvão-Castro et al, 1997;Veit et al, 2006). In previous studies, the HTLV seroprevalence in potential blood donors from the state of Pará ranged from 0.3% (Maneschy et al, 2021) the approach, the antigens used, and the class of antibodies detected by the procedure (Maneschy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Esse vírus faz parte da família Retroviridae e é caracterizado por possuir material genético composto por Ácido Ribonucleico (RNA), sendo este de fita simples e envolvido por um envelope glicoproteico e capsídeo. Além disso, o HTLV possui formato esférico e realiza o processo de replicação por meio da transcriptase reversa, integrasse e protease (OLIVEIRA et al, 2015).…”
Section: Introductionunclassified